2020
DOI: 10.1177/0265407520969896
|View full text |Cite
|
Sign up to set email alerts
|

A combination of insecure attachment patterns in a relationship and its quality: The role of relationship length

Abstract: Most studies confirm that a combination of insecure attachment patterns in a couple has a negative effect on a romantic relationship. However, some research findings suggest otherwise. It is because they do not take account of relationship length as a moderating variable. The aim of this study was to examine the role of relationship length in predicting the effects of a combination of insecure attachment patterns on different aspects of its quality. The study involved 200 heterosexual couples. We used the Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The examination of relationship length among woman who lost a parent yielded a U‐shaped curve: in the first year of the relationship the levels of ASA and anxious attachment were low, peaking between 1 and 5 years, and then declining, reaching their lowest point after 10 years of relationship. The current findings partially support a previous study indicating that when partners are anxiously attached, the quality of the relationship improves with time (Kuncewicz et al., 2021). Furthermore, the current findings partially align with other studies where a U‐shaped association was observed, characterized by higher relationship satisfaction in the early (usually pre‐parental) years of marriage, a decrease in relationship satisfaction during the middle (usually parental) years, and an increase in relationship satisfaction in the later (usually post‐parental) years (Orbuch et al., 1996; Peleg, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The examination of relationship length among woman who lost a parent yielded a U‐shaped curve: in the first year of the relationship the levels of ASA and anxious attachment were low, peaking between 1 and 5 years, and then declining, reaching their lowest point after 10 years of relationship. The current findings partially support a previous study indicating that when partners are anxiously attached, the quality of the relationship improves with time (Kuncewicz et al., 2021). Furthermore, the current findings partially align with other studies where a U‐shaped association was observed, characterized by higher relationship satisfaction in the early (usually pre‐parental) years of marriage, a decrease in relationship satisfaction during the middle (usually parental) years, and an increase in relationship satisfaction in the later (usually post‐parental) years (Orbuch et al., 1996; Peleg, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Conflict, PCR, and EF when comparing groups by relationship length. Shorter relationships in our sample had lower conflict scores than longer ones, used more PCR and had lower scores on EF, a tendency consistent with the literature analyzing the effects of relationship length on several key areas of close and intimate interpersonal functioning related to conflict (Totenhagen et al, 2016;Kuncewicz et al, 2021;Vanderbilt and Solomon, 2022). The results regarding satisfaction with the partner as a function of age, relationship length, and having or not having children are consistent with the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the measurement properties of PN-RQ were not explored depending on the duration of the relationship. For example, partners in the honeymoon phase may assess their relationship in a completely different way than when they are in more difficult phases (Kuncewicz et al, 2020;Reese-Weber, 2005). Taking into account the length or the phases of a relationship, the use of the two-dimensional PN-RQ scale in cross-sectional and longitudinal studies would lead to a better understanding of the developmental dynamics of the quality of relationships.…”
Section: Discussionmentioning
confidence: 99%